Estimating the impact of financial development on poverty in Cameroon using the autoregressive distributed deceleration (ARDL) model for the period (1981-2017) : Memperkirakan dampak pembangunan keuangan terhadap kemiskinan di Kamerun dengan menggunakan model perlambatan terdistribusi autoregresif (ARDL) untuk periode (1981-2017) - Nayf, Asst. Prof. Dr. Yusra Salim; Saleh, Asst. Prof. Dr. Khattab Imran; khaleel, Asst. Prof. Dr. Mustafa ismaeel (Indonesian Journal of Law and Economics Review, 2025)
General Background: Financial development is often seen as a tool for poverty reduction. In Cameroon, its effectiveness remains debated. Specific Background: Despite reforms since the 1980s, poverty—especially in rural areas—persists amid uneven financial access. Knowledge Gap: Empirical evidence on how specific financial indicators affect poverty in Cameroon is limited. Aims: This study analyzes the impact of financial development on poverty using ARDL models for 1981–2017, with per capita consumption as a proxy for poverty. Results: Broad money supply positively affects consumption in both the short and long term, while private sector credit has a negative long-term effect. Inflation reduces consumption, and trade openness is statistically insignificant. Novelty: The study distinguishes between financial indicators, revealing that not all forms of financial development reduce poverty. Implications: Broader financial development must be complemented by inflation control, infrastructure improvements, and inclusive policies to reduce poverty effectively.Highlight : Financial development, particularly broad money supply, significantly influences poverty reduction in both short and long terms. Inflation has a consistently negative effect on per capita consumption, highlighting its role in poverty dynamics. Credit to the private sector does not effectively reduce poverty long-term without supportive infrastructure and policy conditions. Keywords : Financial Development, Poverty, Cameroon, ARDL Model, Inflation